Unveiling neuroprotective mechanisms of diosgenin and pterostilbene in diabetes-associated Alzheimer's disease through multi-target molecular docking approach - Syeda Jabeen Fatima; Devarakonda Krishna Prasad (Shahrekord University of Medical Sciences, 2024)
Introduction: Diabetes mellitus (DM) and Alzheimer's disease (AD) are two highly linked disorders due to their association with the aging population. Several studies have reported the beneficial effects of diosgenin and pterostilbene in treating neurodegenerative diseases. This study aimed to investigate the neuroprotective mechanisms of diosgenin and pterostilbene through molecular docking and dynamics studies and assess their pharmacokinetic parameters. Methods: To understand the link between diabetes and AD, molecular docking of the natural ligands diosgenin and pterostilbene against the specific targets of AD, including β-secretase, glycogen synthetase kinase beta (GSK-3β), gamma-secretase, tumor necrosis factor-alpha (TNF-ɑ), and interleukin-6 (IL-6) was done to find out their binding affinities to explain the molecular mechanisms involved in their neuroprotection. Further molecular dynamics studies and binding energy calculations for the ligands with GSK-3β and β-secretase were carried out to confirm their docking activities. Additionally, pharmacokinetic analysis of these two phytoconstituents was performed by the SWISSADME server. Results: Molecular docking and dynamics studies revealed the good docking activity of diosgenin and pterostilbene with the selected targets. Further, the two phytoconstituents revealed suitable pharmacokinetic parameters along with blood-brain barrier permeability, confirming their druggable nature. Conclusion: This research identified multiple neuroprotective pathways of diosgenin and pterostilbene that might be significant for treating diabetes-associated Alzheimer's disease.